(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The sintering pot test was used to investigate the effect of MgO/Al2O3 ratio in the range of 1.2 to 2.2 on the sintering behavior of iron ore. The main characterization methods of X-ray diffraction (XRD), scanning electron microscopy-energy disperse spectroscopy (SEM-EDS) were employed. In this study, strength, yield, solid fuel consumption, FeO content, reduction degradation index (RDI), and reduction index (RI) were tested and calculated. From the results, it was observed that the strength, yield and reducibility of sinter initially increased then decreased with increasing MgO/Al2O3 ratio from 1.2 to 2.2. The index would reach the peak value with the strength of 70.6% and the yield of 83.81%, respectively, when MgO/Al2O3 ratio was 1.8. The reduction index would reach the peak value of 88.54% with MgO/Al2O3 ratio of 1.6. The FeO content, solid fuel consumption and the RDI+3.15 of sinter increased dramatically with increasing MgO/Al2O3 ratio. When MgO/Al2O3 ratio was up to 2.2, the solid fuel consumption and RDI+3.15 reached a maximum value of 61.93 kg/t and 96.1%, respectively. The form of SFCA was acicular when MgO/Al2O3 ratio was less than 1.6, and then transformed to plate-like which content also reduced. The magnetite increased while hematite decreased with enhancing MgO/Al2O3 ratio.